Clodronate changes neurobiological effects of pulsed magnetic field on diabetic rats with peripheral neuropathy. (September 2013) - Mert, Tufan; Ocal, Isıl; Guzel, A. Irfan; Gunay, Ismail
Abstract : Several studies have reported that pulsed magnetic fields (PMFs) can be a choice of therapy for diabetic peripheral neuropathy. However, the exact underlying mechanism of PMF is still not known. The purpose of this study was, therefore, to investigate the effects of clodronate encapsulated with liposome, a specific agent depleting macrophage, on PMF-treated streptozotocin-induced type I diabetic rats with peripheral neuropathy. Effects of PMF, liposome-encapsulated clodronate (LEC) or their combined treatments were investigated in diabetic rats by measuring the thermal latencies, mechanical thresholds, whole blood glucose levels, serum insulin level, and body mass. In diabetic rats, PMF exhibited a decrease in the blood glucose levels but did not change the serum insulin level. Both mechanical thresholds and thermal latencies of diabetic rats enhanced throughout the PMF treatment. During the PMF treatment, the administration of LEC suppressed the PMF-induced decrease in blood glucose level, PMF-induced increase in mechanical threshold and thermal latencies in diabetic animals. In addition, PMF reduced the LEC-induced increase in insulin levels of diabetic rats. Findings demonstrated that although effects of both PMF alone and LEC alone on diabetic animals are mostly positive, LEC may remove the therapeutic efficacies of PMF in combined treatment.